Formación docente en Chile: percepciones de profesores del sistema escolar y docentes universitarios. (2015)
This article presents the results of research on perceptions of teacher training. The study design is transactional and descriptive, for which an ad hoc survey of two groups was developed: the school sysrtem teachers and academics in the region of Bio Bio in Chile. Its aim is to analyze the perception of these groups on six themes: evaluation, learning, innovation, research, development and relationship university / school / community. The main results show a high evaluation of assessment practices, introducing innovations in the classroom and refinement. The reasearch is carried out by both teachers and university profressors in the school system, although at different frequencies. The university / school / community relations are considered relevant but are not consolidarted. Finally some thoughts arise that link the themes discussed in terms of improving teacher education.